2012
DOI: 10.1074/mcp.m112.021204
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Long Term Calorie Restriction on in Vivo Hepatic Proteostatis: A Novel Combination of Dynamic and Quantitative Proteomics

Abstract: Calorie restriction (CR) promotes longevity. A prevalent mechanistic hypothesis explaining this effect suggests that protein degradation, including mitochondrial autophagy, is increased with CR, removing damaged proteins and improving cellular fitness. At steady state, increased catabolism must be balanced by increasing mitochondrial biogenesis and protein synthesis, resulting in faster protein replacement rates. To test this hypothesis, we measured replacement kinetics and relative concentrations of hundreds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
115
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(128 citation statements)
references
References 55 publications
12
115
1
Order By: Relevance
“…Also expectedly, immunoblots failed to detect evidence for increased expression of the tested glycolytic proteins. Taken together, these data suggest that changes in protein turnover and protein abundance in a system are largely independent parameters, an observation that is consistent with a recent study in 2 H 2 O and SILAC doubly labeled mice (41).…”
Section: Methodssupporting
confidence: 77%
“…Also expectedly, immunoblots failed to detect evidence for increased expression of the tested glycolytic proteins. Taken together, these data suggest that changes in protein turnover and protein abundance in a system are largely independent parameters, an observation that is consistent with a recent study in 2 H 2 O and SILAC doubly labeled mice (41).…”
Section: Methodssupporting
confidence: 77%
“…To capture changes in both the RR constants ( k , fraction new protein per day) and RPS of individual proteins, we combined heavy water labeling with internal S table I sotope La beling in M ammals (SILAM) standards and measured both by LC‐MS/MS. The rate of incorporation of deuterium from heavy water into proteins was used to calculate RRs, as previously described (Price et al ., 2012b). To calculate the RPS of proteins, liver homogenates were spiked with an exogenous heavy‐labeled SILAM standard (derived from the liver of a mouse fully labeled with 15 N).…”
Section: Resultsmentioning
confidence: 99%
“…aRelative to control counterparts.bHomozygous for loss‐of‐function recessive mutation in Pit1 gene.cDuration of intervention taken to be the age of the animals at the time of euthanasia.d25% calorie‐restricted relative to AL.eAdapted from (Price et al ., 2012b). …”
Section: Methodsmentioning
confidence: 99%
“…We (25,(29)(30)(31) and others (32,33) have shown that the second problem can be addressed by combining stable isotope label incorporation with tandem mass spectrometric-based proteomics techniques. In particular, isotope ratio measurements using liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) with quadrupole-time-of-flight (Q-ToF) instruments can be performed in the scan mode on trypsinderived peptides with sufficient analytic accuracy to quantify synthesis rates of hundreds of proteins concurrently after relatively low-level in vivo 2 H 2 O labeling (25,(29)(30)(31). Here, to address the third problem noted above, we report the development and validation of blood test approach for measuring the integrated rate of muscle protein synthesis over days to weeks.…”
Section: Introductionmentioning
confidence: 99%
“…This minimally invasive method can be seen as a virtual biopsy for monitoring skeletal muscle protein synthesis rates. We asked whether the labeling kinetics of proteins in plasma that were synthesized in skeletal muscle, such as creatine kinase M-type (CK-M) and carbonic anhydrase 3 (CA-3) the dynamics of the skeletal muscle proteome, using 2 H 2 O labeling combined with LC-MS/MS analysis (25,(29)(30)(31)(32)(33). In addition, the synthesis and turnover rates of multiple proteins across the proteome (i.e., proteome dynamics) had not previously been characterized in human skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%